Effect of Evodiamine on Collagen-Induced Platelet Activation and Thrombosis. (27th July 2022) - Yang, Xiaona; Leng, Min; Yang, Lihong; Peng, Yunzhu; Wang, Jing; Wang, Qian; Wu, Kun; Zou, Junhua; Wan, Wen; Li, Longjun; Ye, Yujia; Meng, Zhaohui
Abstract : Evodia rutaecarpa has multiple pharmacological effects and is widely used in the prevention and treatment of migraine, diabetes, cardiovascular disease, cancer, and other chronic diseases; however, the pharmacological effects of its active compound evodiamine (Evo) have not been thoroughly investigated. The purpose of this study was to investigate the effects of Evo on antiplatelet activation and thrombosis. We discovered that Evo effectively inhibited collagen-induced platelet activation but had no effect on platelet aggregation caused by activators such as thrombin, ADP, and U46619. Second, we found that Evo effectively inhibited the release of platelet granules induced by collagen. Finally, evodiamine inhibits the transduction of the SFKs/Syk/Akt/PLC γ 2 activation pathway in platelets. According to in vivo studies, Evo significantly prolonged the mesenteric thromboembolism induced by ferric chloride and had no discernible effect on the coagulation function of mice. In conclusion, the antiplatelet and thrombotic effects of Evo discovered in this study provide an experimental basis for the investigation of the pharmacological mechanisms of Evo and the development of antiplatelet drugs.